2013
DOI: 10.1128/jvi.01746-12
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of Experimental CD8+Lymphocyte Depletion in Rhesus Macaques Infected with Simian Immunodeficiency Virus SIVmac239

Abstract: c CD8 ؉ T cells inhibit virus replication in SIV-infected rhesus macaques. However, it is unclear to what extent the viral suppression mediated by CD8؉ T cells reflects direct killing of infected cells as opposed to indirect, noncytolytic mechanisms. In this study, we used functional genomics to investigate noncytolytic mechanisms of in vivo viral suppression mediated by CD8؉ lymphocytes. Eight chronically SIVmac239-infected rhesus macaques underwent CD8؉ lymphocyte depletion, and RNA from whole blood was obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…CD8 ϩ T cells can inhibit HIV/SIV infection through noncytolytic soluble factors (47). Several reports have suggested that these mechanisms may play a major role in the CD8-mediated partial control of SIV infection during primary infection in macaques (48)(49)(50). In vitro infection of mitogen-activated PBMCs has been widely used to reveal the presence of strong activities of these various soluble antiviral factors.…”
Section: Discussionmentioning
confidence: 99%
“…CD8 ϩ T cells can inhibit HIV/SIV infection through noncytolytic soluble factors (47). Several reports have suggested that these mechanisms may play a major role in the CD8-mediated partial control of SIV infection during primary infection in macaques (48)(49)(50). In vitro infection of mitogen-activated PBMCs has been widely used to reveal the presence of strong activities of these various soluble antiviral factors.…”
Section: Discussionmentioning
confidence: 99%
“…These studies were taken as strong, if not the main, evidence for an important effect of CD8+ cells in controlling the virus—and likely were one of the key aspects for the rational to develop CD8+ T‐cell‐based vaccines . Subsequent studies used this experimental approach to try to characterize in more detail the biology of HIV/SIV infection and the mechanisms of action of the CD8+ cells . For example, the contrasting results of depleting these cells in pathogenic models of SIV versus natural hosts of SIV, which do not develop overt disease, were analyzed in multiple studies …”
Section: Cd8+ Cell Depletion Experimentsmentioning
confidence: 99%
“…26 Subsequent studies used this experimental approach to try to characterize in more detail the biology of HIV/ SIV infection and the mechanisms of action of the CD8+ cells. [41][42][43][44][45][46][47] For example, the contrasting results of depleting these cells in pathogenic models of SIV versus natural hosts of SIV, which do not develop overt disease, were analyzed in multiple studies. [48][49][50][51] One of the most common uses of CD8+ cell depletion is to investigate the effects of vaccine protocols.…”
Section: Cd8+ Cell Deple Ti On E Xperimentsmentioning
confidence: 99%
“…We have observed in the nonhuman primate model after depletion of CD8 T cells that even modest (0.5 log) increases in viremia increase ISG expression. 30 It is interesting that, in this study, we observed an ''uncoupling'' of ISG expression and plasma viremia. We also observed a modest but consistent decrease in CD38 and CCR5 RNAs.…”
Section: Figmentioning
confidence: 55%